2013
DOI: 10.4103/0378-6323.110759
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovarian syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is a "multispeciality" disorder suspected in patients with irregular menses and clinical signs of hyperandrogenism such as acne, seborrhoea, hirsutism, irregular menses, infertility, and alopecia. Recently, PCOS has been associated with the metabolic syndrome. Patients may develop obesity, insulin resistance, acanthosis nigricans, Type 2 diabetes, dyslipidemias, hypertension, non-alcoholic liver disease, and obstructive sleep apnoea. Good clinical examination with hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…Met-SR therapy also showed reduction testosterone, increase SHBG levels, ovulatory frequency and menstrual irregularities, which is similar to other studies. 19,20 In the present study we have confirmed that, women with PCOS showed correlation between IR and BMI before and after therapy, and also observed a positive correlation between SHBG and TT with HOMA-IR after six months of Met-SR therapy.…”
Section: Discussionsupporting
confidence: 75%
“…Met-SR therapy also showed reduction testosterone, increase SHBG levels, ovulatory frequency and menstrual irregularities, which is similar to other studies. 19,20 In the present study we have confirmed that, women with PCOS showed correlation between IR and BMI before and after therapy, and also observed a positive correlation between SHBG and TT with HOMA-IR after six months of Met-SR therapy.…”
Section: Discussionsupporting
confidence: 75%
“…Table 1 includes the researches on PCOS done in India. 17 Beena Joshi et al 18 Sanjay Chauhan et al 19 Swetha Balaji et al 20 Pratik Kumar Chatterjee et al 21 Kalavathiet al 22 Sujatha Thathapudi et al 23 Nagaraja Bhuvanashree et al 24 Sudhindra M et al 25 Harmandeep Gill et al 26 B Vijaya Gowri et al 27 Suneet Kumar et al 28 Jisha Varghese et al 29 Sudha Ambigeret al 30 Amar Nagesh Kumar et al 31 Pothiraj Pitchai et al 32 Nina Madnani et al 33 Kar Gayatri et al 34 Shaini joseph et al 35 Anuradha Kalra et al 36 Penagaluru Radha et al 37 Avin S Jamil et al 38 Maniraja Jesintha Mary et al 39 Lilhareet al 40 Vijayan CP and Sonia A. 41 Clinical characteristics of polycystic ovary syndrome in Indian women A cross-sectional study of polycystic ovarian syndrome among adolescent and young girls in Mumbai, India A cross-sectional study of polycystic ovarian syndrome among adolescent and young girls in Mumbai …”
mentioning
confidence: 99%
“…На разных этапах изучения механизмов разви-тия данного заболевания всегда существовало множество теорий возникновения СПЯ, одна-ко в настоящее время среди них наиболее зна-чимыми остаются «центральная» теория СПЯ (теория нарушения секреции гонадотропин-рилизинг-гормона в гипоталамусе) и теория первичной роли гиперинсулинемии [13,14].…”
Section: этиология и патогенез синдрома поликистозных яичниковunclassified